Morphologies, crystallization, and mechanical properties of PLA‐based nanocomposites: Synergistic effects of PEG/HNTs. Issue 18 (10th January 2019) - Jia, Shikui; Yu, Demei; Wang, Zhong; Zhang, Xianyong; Chen, Ligui; Fu, Lei
ABSTRACT: In this study, the compounding modifier poly(ethylene glycol)/halloysite nanotubes (PEG/HNTs) was prepared by supersonic vibration and dynamic vacuuming. A series of poly(lactic acid) (PLA)/PEG and PLA/PEG/HNT composites were fabricated using a twin‐screw extruder. Fourier transform infrared spectroscopy indicated that the hybrid between PEG and HNTs had no evident chemical interaction via supersonic vibration and dynamic vacuuming. The dispersed morphology of the compounding modifier in the PLA matrix was tested by high‐resolution scanning electronic microscopy and transmission electron microscopy. The results showed that the low content of PEG/HNTs presented a good dispersion morphology. The binding energy of the PLA‐based composites was studied through contact angle measurements. The results showed that PEG and PEG/HNTs can decrease the water contact angle of PLA, and that the binding energy between PEG and HNTs is higher than that of PLA/HNTs, which leads to more location of HNTs in the PEG phase. The crystallization behavior of PLA‐based composites was examined by wide‐angle X‐ray diffraction and differential scanning calorimetry. The results suggested that the addition of PEG and PEG/HNTs effectively enhanced the crystallization of PLA and that the diffraction peak intensity of the PLA‐based composites reached a maximum when the content of PEG/HNTs was 1.2 wt %. The spherulite morphology indicated that the addition of PEG resulted in perfect spherulites. The mechanical properties of PLA‐based composites were analyzed with a universal testing machine and impact tester, which confirmed that the tensile strength and impact strength of the PLA‐based composites increased slightly when the content of the PEG/HNT modifier was 1.2 wt %, while the tensile modulus of the PLA‐based composites increased distinctly. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47385. Abstract :